Koima, a new genus of nemacheilid loach from the Western Ghats, India (Cypriniformes: Nemacheilidae) - Anoop, V.k.; Dahanukar, Neelesh; Raghavan, Rajeev (Zootaxa, 2024)
Koima, a new genus of nemacheilid loach, is described for Mesonoemacheilus remadevii Shaji 2002, and Nemacheilus monilis Hora 1921, both of which are endemic to the Western Ghats of southern peninsular India. Koima is distinguished from all other genera of family Nemacheilidae by its unique colour pattern comprising a yellowish-brown ground colour, single row of black spots on lateral line, all fins hyaline, and absence of a uniform banding pattern on dorsal side. Koima remadevii was initially identified as a species of Mesonoemacheilus Bănărescu & Nalbant 1982, from which it can be distinguished by the presence of a lower adipose crest, and an absence of a banding pattern on the dorsal side and on the caudal fin, while Koima monilis was initially identified as a species of Nemacheilus Bleeker 1863, from which it can be distinguished by the presence of a lower adipose crest, a narrow and deeply incised upper lip and having the fins hyaline. In the multi-gene phylogenetic analysis based on concatenated mitochondrial and nuclear gene sequences, Koima remadevii and K. monilis were recovered in a monophyletic group, sister to the endemic peninsular Indian nemacheilid, Schistura denisoni. Resolution of the identity of Koima remadevii and K. monilis contributes to our understanding of the phylogenetics of family Nemacheilidae, which is widely considered to be a polyphyletic group.